2021
DOI: 10.1590/0034-7167-2019-0535
|View full text |Cite|
|
Sign up to set email alerts
|

Burnout Syndrome and Associated Factors in Intensive Care Unit Nurses

Abstract: Objective: to estimate prevalence and factors associated with Burnout Syndrome in intensive care nurses in a city in the state of Bahia. Methods: a cross-sectional, population-based study carried out with 65 intensive care nurses through a self-administered questionnaire, from July to November 2016, containing sociodemographic data, lifestyle, work characteristics. To define burnout syndrome, the Maslach Burnout Inventory was used. Results: Burnout Syndrome prevalence was 53.6%, an association was observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 18 publications
1
10
3
4
Order By: Relevance
“…There was a higher percentage (25.6%) of workers with another employment relationship in Hospital C, adjusted residue analysis was significant and indicates that in this hospital there were more professionals with another job than expected, being also the institution with younger workers, with an average age of 32.7 (±8.7) years, an average of 36 months of professional experience and 24 months of work at the institution, indicating professionals at the beginning of their career. The employment relationship data contrasts with another study that found a percentage of 64% of workers with another employment relationship (15) .…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…There was a higher percentage (25.6%) of workers with another employment relationship in Hospital C, adjusted residue analysis was significant and indicates that in this hospital there were more professionals with another job than expected, being also the institution with younger workers, with an average age of 32.7 (±8.7) years, an average of 36 months of professional experience and 24 months of work at the institution, indicating professionals at the beginning of their career. The employment relationship data contrasts with another study that found a percentage of 64% of workers with another employment relationship (15) .…”
Section: Discussioncontrasting
confidence: 98%
“…Likewise, married/partner marital status was also predominant; however, there was a statistical difference between Hospitals A and D, and the former stood out with a higher percentage of singles and this institution had on average four years younger workers. The mean age in the studied sample that ranged from 32.7 (±8.7) to 40.7 (±8.8) years is similar to other Brazilian studies, which describe nursing professionals, predominantly, in the age group between 30-40 years (12)(13)(14)(15) . The identification of higher mean age and working time at Hospital D, with significant differences in relation to the others, corroborates the results of previous investigations (12,16) , which describe this trend in university hospitals.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Researchers have shown that doctors and nurses alike are tired and overburdened with work challenges, such as high patient load and ethical, medical, and legal responsibilities [2,3]. Reported burnout levels have been reported to be often higher than 50% [4][5][6][7][8][9]. Fatigue and overload are also characteristics of nurses whose burnout stems from socioeconomical factors, as well as hours of work, numbers of patients, job title, and level of education [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Reported burnout levels have been reported to be often higher than 50% [4][5][6][7][8][9]. Fatigue and overload are also characteristics of nurses whose burnout stems from socioeconomical factors, as well as hours of work, numbers of patients, job title, and level of education [8,10,11].…”
Section: Introductionmentioning
confidence: 99%